Effect of MoO3 on The Radiation Shielding Properties of Bismuth Boro-Tellurite Glass (B2O3-TeO2-Bi2O3-Li2O): Theoretical and Simulation Studies - O. A. Putra; R. H. Asiah; H. Sutanto; S. Faniandari; E. B. Yutomo (National Research and Innovation Agency, 2026)
This study aims to evaluate the efficiency of bismuth boro-tellurite glass modified with molybdenum oxide (MoO3) as a gamma-ray shielding material in the (50-x)B2O3-10TeO2-30Bi2O3-10Li2O-xMoO3 (x = 0, 4, 8, 12, and 16 mol%) glass system. Five designed compositions (x = 0-16 mol%) were evaluated over 0.01-15 MeV using XCOM (NIST) and Phy-X/PSD for derived shielding metrics. The calculation results from both programs agreed closely with a maximum difference of only 0.037%, confirming numerical consistency of MAC across tools. Estimated glass density increased with MoO3 content from 5.666 to 5.948 g/cm3 (BBTM1 to BBTM5), which raised LAC and improved thickness indicators. The results showed that at 0.05 MeV the highest LAC was recorded for BBTM5 (38.085 cm-1) compared with BBTM1-BBTM4 (35.364-37.409 cm-1), and at 1.00 MeV the HVL decreased from 1.789 cm (BBTM1) to 1.736 cm (BBTM5). Sample BBTM5, with the highest MoO3 concentration, consistently exhibited higher LAC and larger Zeff/Neff across energies, and a lower Transmission Factor (TF) across representative radioisotope energies (0.662-2.506 MeV), indicating superior gamma-ray shielding effectiveness.